Zwitterionic Hydrobromic Acid Carriers for the Synthesis of 2‐Bromopropionic Acid from Lactide. Issue 6 (26th February 2018) - Kehrer, Matthias; Mehler, Julian; Taccardi, Nicola; Nagengast, Jens; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob
Abstract: A convenient and highly efficient way of synthesizing 2‐bromopropionic acid (2‐BrPA) from lactide is presented. The procedure uses ionic liquids obtained from the addition of HBr to ammonium‐based zwitterions as the solvent and bromination agent. The buffered HBr acidity, high polarity, and charge stabilizing character of the ionic liquid (IL) enable the synthesis of 2‐BrPA with excellent selectivity. The best results are obtained with an imidazolium‐based IL, that is, 1‐(4‐butanesulfonic acid)‐3‐methylimidazolium bromide ([MIMBS]Br). The HBr loading and water content of the IL are crucial parameters for the bromination reaction. The formed 2‐BrPA product can be selectively isolated by extraction from the IL, and the unconverted substrate remains in the [MIMBS]Br IL for the next run. Successful recycling of the IL over four cycles is demonstrated. Abstract : A good tailor : The synthesis of 2‐bromopropionic acid (2‐BrPA) from lactide by using zwitterionic HBr carriers is presented. The reaction is performed in ionic liquids (ILs) that serve as both the solvent and bromination agent. The character of the IL reaction matrix enables the synthesis of 2‐BrPA with excellent selectivity. Thus, 2‐BrPA can be produced selectively from biorenewable feedstock.